High-resolution melting curve analysis to identify sex in papaya (Carica papaya L.) - Barrantes-Santamaría, Walter (2022)
Introduction. The sexing of papaya plants (Carica papaya L.) in commercial plantations is usually done visually once the plant emits the flower. There are also biotechnological procedures such as the Polymerase Chain Reaction (PCR), used to detect the sex of papaya at early ages, however, both methods mentioned above present a series of drawbacks, among them false positives. Objective. To identify sex in papaya seedlings using SNP (Single Nucleotide Polymorphism) markers with a high precision. Materials and Methods. The research was carried out at the Fabio Baudrit Moreno Agricultural Experiment Station of the Universidad de Costa Rica, during the months of February to October, 2020. Eight SNP markers were evaluated in papaya plants of known sex using the HRMA (acronym in English: High Resolution Melting Analysis) technique, the best one was chosen and reevaluated in two populations of the genetic improvement program of this crop, then the sexed plants were sown in the field to compare the molecular sexing with the current field sexing. Results. Several of the SNP markers evaluated were polymorphic and could be used to identify sex in papaya, however, the marker CpSERK_HRM_34704 was the one that most closely matched the selection criteria. Conclusion. In the case of the papaya hybrid Pococi and related breeding populations, the marker CpSERK_HRM_34704 showed 100 % precision between the molecular sexing of the seedlings in the nursery using the HRM technique and the current sex of the same plants planted in the field.